The Position of the Heritage Property Center (BHP) in Providing Legal Protection for the Civil Rights of Persons in Custody and the Child in Custody - Budiarti, Lilik; Hidayati, Rahmatul; Sunardi, Sunardi (Journal of Law, Politic and Humanities, 2025)
This study uses normative juridical research, using the statute approach, conceptual approach, and historical approach. This thesis is studied to analyze all laws and regulations related to the administration, guardianship, duties and functions of BHP. In order to analyze the position of BHP in providing legal protection for the civil rights of people in custody and children in guardianship, namely as supervisors and guardians. as well as analyzing the legal consequences of a Notary deed or PPAT that contains a determination of custody and guardianship and is not notified or registered at BHP. Legal consequences of the Notary deed or PPAT, the act can be declared to violate Article 418 of the Civil Code, thus the deed can be declared null and void or worthless. So that this of course causes harm to the parties, for that the parties can file a civil lawsuit with a Notary or PPAT to be demanded for compensation for the losses that have been incurred from the making of the deed and can be administratively dismissed. To avoid the problems mentioned above, synergy and cooperation between all parties is needed, the Court, Dukcapil, BPN, Notary and PPAT and the Government also immediately issue a law that clearly regulates the affirmation of the Registration of Court Determination at BHP and strict sanctions if it is violated.